2015
DOI: 10.1113/jp271432
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline goes nuclear: epigenetic modifications during long‐lasting synaptic potentiation triggered by activation of β‐adrenergic receptors

Abstract: Key pointsr Transcription is recruited by noradrenaline in the hippocampus. r Epigenetic mechanisms are recruited by hippocampal noradrenergic receptor activation. r Epigenetic regulation by noradrenaline offers a novel mechanism for long-term potentiation Abstract Noradrenaline (NA) is a neuromodulator that can effect long-lasting changes in synaptic strength such as long-term potentiation (LTP), a putative cellular mechanism for memory formation in the mammalian brain. Persistent LTP requires alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 96 publications
3
39
0
1
Order By: Relevance
“…33 Catecholamine-synthesizing neurons may be central to these processes: norepinephrine has been demonstrated, in hippocampal memory cells, to induce long-term synaptic potentiation via epigenetic mechanisms. 34 One region richly populated by adrenergic neurons is the rostral ventrolateral medulla, a key autonomic node with projections to hypothalamic regions and the spinal cord. 35 A second, intimately involved in arousal and alertness, is the locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Catecholamine-synthesizing neurons may be central to these processes: norepinephrine has been demonstrated, in hippocampal memory cells, to induce long-term synaptic potentiation via epigenetic mechanisms. 34 One region richly populated by adrenergic neurons is the rostral ventrolateral medulla, a key autonomic node with projections to hypothalamic regions and the spinal cord. 35 A second, intimately involved in arousal and alertness, is the locus coeruleus.…”
Section: Discussionmentioning
confidence: 99%
“…33 Las neuronas que sintetizan catecolaminas pueden ser centrales en estos procesos: se ha demostrado que la noradrenalina, en las células de memoria del hipocampo, induce potenciación a largo plazo mediante mecanismos epigenéticos. 34 La porción rostral ventrolateral del bulbo raquídeo es una región intensamente poblada por neuronas adrenérgicas y es un nudo autónomo clave con proyecciones a regiones hipotalámicas y a la médula espinal. 35 El locus coeruleus es una segunda región íntimamente involucrada en el despertar y el estado de vigilancia.…”
Section: Discussionunclassified
“…A recent study showed that tDCS induces epigenetic changes, including the BDNF locus in the mouse brain 12 . Considering another recent report that noradrenergic β receptor signaling promotes NMDAR-dependent long-term potentiation through epigenetic changes in neurons, 40 tDCS-induced noradrenergic signaling conceivably contributes to neural plasticity and epigenetic modifications, in consort with the astrocyte-mediated signaling.…”
Section: Introductionmentioning
confidence: 99%
“…One type of hippocampal synaptic plasticity is long-term potentiation (LTP) (Bliss and Lømo 1973). LTP is believed to be a cellular mechanism for memory formation in the mammalian brain (Bliss and Collingridge 1993;Bourtchuladze et al 1994;Ji et al 2003a;Gelinas and Nguyen 2005;Whitlock et al 2006; for review, see Martin et al 2000), and it can be sustained by treating in vitro hippocampal slices with either a β-AR agonist, isoproterenol (ISO) (Thomas et al 1996;Katsuki et al 1997;Gelinas and Nguyen 2005), or with the natural β-AR ligand, NE (Katsuki et al 1997;Hu et al 2007;Maity et al 2016;for review, see O'Dell et al 2015). Furthermore, β-AR activation by ISO or NE boosts the endurance of LTP by activating signaling kinases to modulate translation initiation and increase the synthesis of specific proteins (Winder et al 1999;Klann et al 2004;Gelinas et al 2007;Maity et al 2015;for review, see O'Dell et al 2015).…”
mentioning
confidence: 99%